Temozolomide Is a Potential Therapeutic Tool for Patients With Metastatic Pheochromocytoma/Paraganglioma—Case Report and Review of the Literature - Tong, Anli; Li, Ming; Cui, Yunying; Ma, Xiaosen; Wang, Huiping; Li, Yuxiu (Frontiers in Endocrinology, 2020)
Context: Metastatic pheochromocytoma/paraganglioma (MPP) therapy mainly involves radionuclide therapy, chemotherapy and targeted therapy. In recent years, temozolomide (TMZ) showed great promise in some MMP patients, especially those with SDHB germline mutation. We reported a patient with MPP who did not have any known germline genetic change and responded remarkably well to TMZ monotherapy. Case presentation: The patient was a 41-year-old woman with local and distant recurrence (soft tissues and bone metastases) of retroperitoneal paraganglioma. She suffered from dizziness, palpitation, sweating, weight loss and constipation, with the blood pressure fluctuating substantially from 130/100 mmHg to 190/120 mmHg, although she was on phenoxybenzamine and metoprolol medication. The patient showed clinical and radiological response after 3-cycle TMZ therapy. Upon 15 cycles of TMZ therapy, her symptoms were dramatically alleviated, urinary norepinephrine excretion decreased from 1840 μg/24h to 206 μg/24 h, and CT showed that the lesions further shrank. Molecular profiling of the tumor tissue of the patient revealed hypermethylation of the O6-methylguanine-DNA-methyltransferase (MGMT) promoter and a negative immunostaining for MGMT. Globally, only 26 cases of MPP treated with TMZ have been described so far. TMZ is effective, especially in patients with SDHB mutation, which can be explained by the silencing of MGMT expression as a consequence of MGMT promoter hypermethylation in SDHB-mutated tumors. Although, in general, patients with SDHB mutation or MGMT promoter hypermethylation have better response to TMZ, there are also exceptions. Severe side effects are uncommon, with only 17.4% patients experiencing Grade 3 toxicities, including lymphopenia and hypertension. Conclusions: TMZ is effective and safe in MPP patients, and works better on patients with SDHB-related MPP. Measurement of MGMT expression might help assess the tumor sensitivity to TMZ but this needs further systematic investigation.